PERAN GURU BK DALAM MENGATASI SELF CONFIDENCE PADA PESERTA DIDIK STUTTERING MELALUI KONSELING INDIVIDU PENDEKATAN CLIENT CENTERED THERAPY (CCT) DI SMP NEGERI 2 SLOGIRI TAHUN PELAJARAN 2025/2026 - Hiska, Aulia; Eko Adi; Ahmad Jawandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the role of Guidance and Counseling (BK) teachers in enhancing self-confidence among students who experience stuttering through individual counseling services using the Client-Centered Therapy (CCT) approach at SMP Negeri 2 Selogiri during the 2025/2026 academic year.This research employed a qualitative descriptive design. The data were collected through interviews, observations, and document analysis. Data validity was ensured through triangulation technique. Data analysis process consisted of four stages: data collection, data reduction, data display, and conclusion drawing.Based on the results of the study, it was found that the role of BK teachers through individual counseling using the Client-Centered Therapy (CCT) approach play a significant role in improving the self-confidence of students who experience stuttering. Improvements were observed in students’ behavioral and emotional aspects, including increased openness in expressing feelings, greater confidence in articulating opinions, and enhanced social interaction within the school environment. The Client-Centered Therapy approach facilitates students with opportunities to understand themselves, accept their conditions, and recognition of their potential. Moreover, the role of BK teachers as facilitators, empathetic listeners, and supportive figures contributes to the creation of a safe and comfortable counseling environment, which encourages students’ optimal personal development.